The Female Entrepreneur Case Study: Start-Up in Romania - Cristina Elena BIGIOI; Maria Nicoleta CRISTEA (Communications of International Proceedings, 2020)
Entrepreneurs are an important part of the economy. They allow the development of goods and services. Lately, more and more people are trying to develop a personal business, giving up the job they had, or at the same time with the job that ensures a stable income.Entrepreneurship has also developed among women internationally. The position of women is becoming more and more important, the need for her involvement in public life and in the management of organizations being necessary and undisputed.The present study follows the evolution of the winning companies of a competition regarding the granted subsidies, companies that have as associate a woman. The study shows that very few of the 21 companies have managed to achieve performance in the 5 years since they received a small financing in the form of non-reimbursable funds.
Keywords: Female Entrepreneurs; Performance; Non-Reimbursable Funds